Community Participation in the Enforcement of Aceh Qanun Number 6 of 2014 concerning the Law of Jinayat in the Case of Online Gambling Games in Rikit Bur Village, Bukit Tusam District, Southeast Aceh Regency - Husni A. Jalil; Mayang Rina (Bulletin of Islamic Research, 2025)
The rampant behavior of playing online gambling among the people of Rikit Bur Village has had a bad impact on people's lives, therefore law enforcement should take a role in overcoming it, one of which is the enforcement of Qanun Aceh Number 6 of 2014 concerning the Jinayat Law. This study aims to find out the enforcement of Qanun Aceh Number 6 of 2014 concerning the Jinayat Law on online gambling games and the participation of the community in the enforcement of the Aceh Qanun Number 6 of 2014 concerning the Jinayat Law to handle the behavior of online gambling games in Rikit Bur Village. This research uses a legal approach (status approach) and the type is sociological juridical. Data collection was carried out by observation, interviews, documentation and literature studies. The results of the study are known that the enforcement of Qanun Aceh Number 6 of 2014 concerning the Law of Jinayat against Online Gambling Games in Rikit Bur Village was carried out by providing counseling on Qanun Aceh Number 6 of 2014 concerning the Law of Jinayat for the community and online gambling perpetrators, preventing and taking action against online gambling perpetrators both preventively and repressively to making arrests for online gambling game perpetrators after previous efforts were ignored by gamblers Online. Community participation in the enforcement of Qanun Aceh Number 6 of 2014 concerning the Jinayat Law to handle the behavior of online gambling games in Rikit Bur Village is carried out by participating in the socialization and counseling of the qanun to the community, participating in controlling community behavior, and reprimanding people who play online gambling.